2016
DOI: 10.1038/srep36978
|View full text |Cite
|
Sign up to set email alerts
|

An Antarctic molluscan biomineralisation tool-kit

Abstract: The Antarctic clam Laternula elliptica lives almost permanently below 0 °C and therefore is a valuable and tractable model to study the mechanisms of biomineralisation in cold water. The present study employed a multidisciplinary approach using histology, immunohistochemistry, electron microscopy, proteomics and gene expression to investigate this process. Thirty seven proteins were identified via proteomic extraction of the nacreous shell layer, including two not previously found in nacre; a novel T-rich Muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
(72 reference statements)
0
20
0
Order By: Relevance
“… Biomineralization modules of the GRN ground-truthed with previously published in situ hybridization in vivo expression data. ( A ) Schematic of L.elliptica mantle anatomy and shell [modified from Sleight et al (2016) ]. ( B ) Module 1 regulates the secretion of extracellular matrix proteins required for biomineralization of the nacreous shell layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Biomineralization modules of the GRN ground-truthed with previously published in situ hybridization in vivo expression data. ( A ) Schematic of L.elliptica mantle anatomy and shell [modified from Sleight et al (2016) ]. ( B ) Module 1 regulates the secretion of extracellular matrix proteins required for biomineralization of the nacreous shell layer.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, mantle transcriptomes and shell proteomes have been described for many mollusc species ( Clark et al , 2010 ; Jackson et al , 2006; Marie et al , 2010 , 2013 ), in addition to RNA-Seq shell damage-repair experiments ( Huning et al , 2016 ; Sleight et al , 2015 ). A handful of candidate biomineralization genes have been identified and further characterized with a combination of qPCR, in situ hybridizations and protein immune-detection ( Fang et al , 2012 ; Marie et al , 2012 ; Sleight et al , 2016 ). Annotation rates vary considerably between mollusc species from around 32–34% in the Antarctic clam and the blue mussel ( Mytilus edulis) to 87% in the Pacific oyster ( Sleight et al , 2015 ; Yarra et al , 2016 ), which often constrains research efforts to previously characterized, annotated sequences.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of SMPs have been identified in the past decade using proteomics, transcriptomics and, to a lesser extent, genomics, which allowed researchers to identify and compare the shell proteomes ('shellomes') of different taxa. Most of these studies focused on mother-of-pearl shells (Marie et al, 2017(Marie et al, , 2013aRamos-Silva et al, 2012;Yarra et al, 2016), shedding light on some characteristics of shell proteins (Arivalagan et al, 2017;Sleight et al, 2016). One interesting feature, is the widespread occurrence of low complexity domains/ repetitive low complexity domains (LCDs/RLCDs) (Kocot et al, 2016;Marin et al, 2016Marin et al, , 2014) -these were identified in proteins associated with nacre (Jackson et al, 2010;McDougall et al, 2013;Sakalauskaite et al, 2019) but were also found in shell proteomes associated with other microstructures (Marie et al, 2013a), suggesting that these domains likely play a role in mineral binding and in providing flexibility (Sarashina and Endo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the generation of EST libraries and NGS data revealed the true extent of mantle gene expression modularity (e.g. Jackson et al ., 2006; Jackson, Worheide, & Degnan, 2007; Gardner et al ., 2011; Sleight et al ., 2016; Herlitze et al ., 2018). The most recent example was in Lymnaea stagnalis , in which 34 gene transcripts were localized by in situ hybridization across different developmental stages (trochophore larvae and juveniles) and in adult tissue.…”
Section: Biomineralization Genes and Proteins: Functionalitymentioning
confidence: 99%
“…Such studies will play essential roles in assigning putative biomineralization functions to genes with no associated annotation, only mantle‐specific expression (e.g. Sleight et al ., 2016).…”
Section: Biomineralization Genes and Proteins: Functionalitymentioning
confidence: 99%